Design and application of a single‐tuned passive harmonic filter to suppress harmonic distortion and resonance for railway traction power systems—A case study - Wei‐Hsiang Ko; Martti Tuomainen (IET Electrical Systems in Transportation)
Abstract The railway traction loads produce massive harmonics that are injected directly into the traction power system. This causes serious waveform distortion in the supply voltage and even invokes a harmonic parallel resonance, which may lead to significant harmonic current and voltage amplification. Consequently, severe electrical equipment failures and feeder tripping problems occurred frequently in the traction substation. A clear harmonic parallel resonance at a 27.5‐kV feeder can be observed from the field measurement result of the traction substation without filter banks. This paper proposes a high‐performance single‐tuned 3rd passive filter for harmonic mitigation and harmonic resonance suppression in the traction power system. In the ST filter design process, the impact of the quality factor (Qf) design of the filter reactor on the filtering performance is considered. Furthermore, the driving point impedance as seen from the traction load is also studied. The design and the engineering consideration of the harmonic filter are also presented, which comply with the recommendations of the IEEE and IEC standards. Besides, the unbalance‐current protection of a capacitor bank is introduced in this paper. Finally, the proposed filter is implemented in an actual traction substation, from the field measurement results; the proposed harmonic filter delivers very good performance.